(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article examines the translation of historical works, its history and the problems that arise today. The translation of historical works has its own complexities and requires translators to have a deep knowledge of not only the language, but also the culture and historical context. The terms, phraseologisms, cultural, social and historical contexts used in historical works play an important role in the translation process. The article analyzes the difficulties that arise in the translation of historical works, old and new translation methods. It also presents ideas about the changes that the translation of historical works is undergoing today and new approaches that have emerged in modern translation studies.